Japan's new ruralities
1 online resource.
Keywords: "Seeking to challenge negative perceptions within Japanese media and politics on the future of the countryside, the contributors to this book present a counter-argument to the inevitable demise of rural society. Contrary to the dominant argument, which holds outmigration and demographic hyper-aging as primarily responsible for rural decline, this book highlights the spatial dimension of power differences behind uneven development in contemporary Japan. Including many fieldwork-based case studies, the chapters discuss topics such as corporate farming, local energy systems and public health-care, examining the constraints and possibilities of rural self-determination under the centripetal impact of forces located both in and outside of the country. Focusing on asymmetries of power to explore regional autonomy and heteronomy, it also examines 'peripheralization' and the 'global countryside', two recent theoretical contributions to the field, as a common framework. Japan's New Ruralities addresses the complexity of rural decline in the context of debates on globalization and power differences. As such, it will be of interest to students and scholars of sociology, anthropology, human geography and politics, as well as Japanese Studies"--